Heart rate changes associated with the different types of leg movements during sleep in children, adolescents and adults with restless legs syndrome. (6th May 2021) - Ferri, Raffaele; Silvani, Alessandro; Mogavero, Maria P.; Rundo, Francesco; Bruni, Oliviero; Picchietti, Daniel L.; DelRosso, Lourdes M.
Abstract: The objective of this study was to describe in detail the heart rate changes accompanying short‐interval leg movements during sleep, periodic leg movements during sleep, and isolated leg movements during sleep in children and adolescents with restless legs syndrome, and to compare them with the same findings in adults with restless legs syndrome. We analysed time series of R‐R intervals synchronized to the onset of short‐interval leg movements during sleep, periodic leg movements during sleep or isolated leg movements during sleep that entailed an arousal during non‐rapid‐eye‐movement sleep. We assessed cardiac activation based on the heart rate changes with respect to baseline during non‐rapid‐eye‐movement sleep without leg movements. All types of leg movements recorded during sleep were accompanied by important heart rate changes also in children, with an overall impact similar to that observed in adults. In all age groups, heart rate changes accompanying short‐interval leg movements during sleep were constituted by a tachycardia, without a subsequent relative bradycardia, that was instead evident for periodic leg movements during sleep and isolated leg movements during sleep. Moreover, an age‐related decline of the relative bradycardia following the heart rate increase, in association with periodic leg movements during sleep and isolated leg movements during sleep, was observed. Our findings show that important heart rate changes accompany all leg movements during sleep at all ages in restless legs syndrome, with significant age‐related differences. This information represents an important contribution to the ongoing scientific debate on the possibility and opportunity to treat periodic leg movements during sleep.